The Effect of Media Composition on The Change of Bag Log Waste Composition and Production of Oyster Mushroom - Sarono Sarono; Yana Sukaryana; Sri Astuti (The University of Lampung, 2024)
OPEFB has low biodegradability so its utilization is very limited. Oyster mushrooms are mushrooms that are capable of producing enzymes capable of degrading cellulose, hemicellulose, and lignin contained in) OPEFB. The research objective was to determine the effect of the composition of the growing media on the production of oyster mushrooms and changes in the composition of the resulting baglog waste. The study was carried out with the combination treatment of rubber wood and OPEFB, with levels: (a) 100% rubber wood powder and 0% OPEFB, (b) 75% rubber wood powder and 25% OPEFB, (c) 50% rubber wood powder and OPEFB 50%, (d) 25% rubber wood powder and 75% OPEFB, (e) 0% rubber wood powder and 100% OPEFB. Observation of raw material composition, mycelia growth, wet weight of the fungus, biological efficiency, changes in lignin content, cellulose, and hemicellulose before and after being used as a growing medium for oyster mushrooms. The results showed that the fastest mycelial growth occurred in the use of 100% OPEFB media. The highest oyster mushroom production occurred in the media 100% rubber sawdust. The higher the wet weight of the oyster mushrooms produced, the less the weight of the baglog waste produced. The oyster mushroom fermentation process for 60 days was able to reduce the content of 3.39% cellulose, 11.01% hemicellulose, and 1.98% lignin. Keywords: OPEFB, Oyster Mushroom, Cellulose, Hemicellulose, Lignin